A thermally-invariant, additively manufactured, high-power graphene resistor for flexible electronics. (19th April 2017) - Michel, Monica; Biswas, Chandan; Tiwary, Chandra S; Saenz, Gustavo A; Hossain, Ridwan F; Ajayan, Pulickel; Kaul, Anupama B
Abstract: Solution processed two-dimensional (2D) layered materials and their integration with additive manufacturing techniques, such as ink-jet printing, is a facile approach for incorporating these exotic materials into device platforms for flexible electronics. In this work, graphene ink formulations are successfully utilized toward the design and fabrication of high-power resistive structures that are printed on both rigid and flexible substrates and have the potential to deliver close to 10 W of power. A near-flat, negative temperature coefficient of resistivity (TCR) is measured with an activation energy E a 2.4 meV for electron hopping, which is 100× lower compared to E a values for high TCR materials. The TCR and E a values are amongst the lowest reported for 2D layered material systems. The thermal-invariance of resistivity for such high-power graphene printed resistors is attractive for applications, for example to provide a stable heating source for flexible electronics over extreme thermal environments. The transport characteristics of the ink-jet printed features is modeled as a composite structure in order to explain the thermal response which appears to be mediated via defects in the sonicated graphite, and correlates well to inferences made from Raman spectroscopy and transmission electron microscopy analysis conducted on the printed graphene structures. In order to fabricate such functional structures with ink-jet printing, the active nozzle number, printing passes, and annealing conditions are shown to play an important role to determine line resolution, and also dictate the morphological and electronic transport characteristics of the printed graphene features.